Complications of surgical treatment for distal biceps tendon ruptures: current challenges and solutions - Lisunov, M. S.; Golovakha, M. L.; Головаха, Максим Леонідович (My University, 2024)
The paper deals with the current problems and complications of surgical treatment of ruptures of the distal biceps brachii tendon (DBT). The main complications, such as neuropathy, heterotopic ossification, repeated tears, compartment syndrome and “hanging hand” syndrome, are highlighted. Their causes, frequency of occurrence and possible methods of prevention are analyzed. Particular attention is paid to the improvement of fixation techniques, the use of regenerative technologies and the introduction of minimally invasive techniques. Solutions are proposed, including optimization of surgical interventions, standardization of rehabilitation programs and the use of innovative materials. The need for further research to reduce the incidence of complications and improve functional outcomes is emphasized.
Keywords: biceps brachii muscle; tendon injuries; conservative treatment; surgical treatment; tendon refixation; biceps tendon